Intact Forest in Selective Logging Landscapes in the Tropics - Putz, Francis E.; Baker, Tracy; Griscom, Bronson W.; Gopalakrishna, Trisha; Roopsind, Anand; Umunay, Peter M.; Zalman, Joey; Ellis, Edward A.; Ruslandi,; Ellis, Peter W. (Frontiers in Forests and Global Change, 2019)
The selective logging that characterizes most timber extraction operations in the tropics leaves large patches of logging blocks (i.e., areas allocated for harvesting) intact, with no direct impacts of the harvest. For example, in the ~10,000 ha we sampled sampled in 48 forest management enterprises in Africa (Gabon, Republic of Congo, and the Democratic Republic of Congo), Indonesia, Suriname, and Mexico, an average of 57% (range 22-97%) of the area in logging blocks was not directly affected by timber harvests. The proportion of intact forest within logging blocks decreased very slightly with increases in harvest intensity in the accessed portion of the logging blocks (9-86 m3 ha-1) but decreased strongly with harvest intensity in entire logging blocks (0.3-48.2 m3 ha-1). More forest was left intact in areas farther from roads, on slopes >40%, and within 25 m of perennial streams, but the effect sizes of each of these variables was small (~8%). It is less clear how much of the intact forest left after one harvest will remain intact through the next. Conservation benefits without reductions in timber yields will derive from better management planning so that sensitive and ecologically critical areas, such as steep slopes and riparian buffers, constitute permanent reserves of intact forest in selectively logged landscapes in the tropics.